ANALISIS PENGARUH PRODUK DOMESTIK REGIONAL BRUTO PERKAPITA DAN PENGELUARAN PEMERINTAH TERHADAP INFLASI KOTA DENPASAR PERIODE TAHUN 1994-2013 - Dewi, Feby Shinta; Indrajaya, I Gusti Bagus; Djayastra, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 1, Januari 2017 (pp. 1 - 114), 2017)
I ncreased economic growth had an impact on changing people's income, changes in the price structure, change the pattern of supply of goods and services, as well as changes in consumption patterns. Inflation or developments subsequent price used as a benchmark of stability of the regional economy in a given period. The purpose of this study was to determine the effect of Gross Regional Domestic Product (GDP) per capita and government spending on inflation. This research was conducted in Denpasar by using quantitative and qualitative data. Source data used is secondary data with doumentasi method. The analysis technique used is multiple linear regression. Based on the analysis found that the Gross Domestic Product (GDP) per capita is positive and significant effect on inflation. While government spending significant negative effect terhdap inflation. Relationships variable GRDP per capita and relatively high government spending on inflation. The GDP per capita and government spending tends to vary a change of variable inflation was only 66.8 per cent and the remaining 33.2 percent is determined by other variables.
Keywords: PDRB,pengeluaran pemerintah, inflasi